Case Report: Tracheobronchomalacia after a two-stage surgical approach to treat congenital diaphragmatic hernia with hepatopulmonary fusion - Kanda, Juri; Mukai, Takeo; Irisa, Chiharu; Ibi, Kyosuke; Matsuda, Rina; Morita, Kaori; Ishiguro, Akio; Ikemura, Masako; Yamada, Yosuke; Hasegawa, Hisaya; Fujishiro, Jun; Takahashi, Naoto (Frontiers in Pediatrics, 2025)
Hepatopulmonary fusion (HPF) is a rare comorbidity of right-sided congenital diaphragmatic hernia (CDH). The mortality rate of CDH with HPF is high, and the optimal approach and timing for surgical intervention remain unclear. Previous studies have reported the importance of avoiding massive intraoperative bleeding, managing pulmonary hypertension, and evaluating abnormal vascular communication in the management of CDH with HPF. However, airway involvement has rarely been documented. Here, we report a case of tracheobronchomalacia (TBM) following a two-stage surgical approach to treat CDH with HPF. The patient was diagnosed with right-sided CDH during gestation. CDH repair was attempted on day of life (DOL) 2. HPF was found intraoperatively, but was left unseparated to avoid massive bleeding. After excluding abnormal vascular communication on computed tomography, a second surgery was performed on DOL 28. HPF was successfully separated, and the right thoracic and abdominal cavities were separated using a polytetrafluoroethylene patch. The patient was extubated on DOL 41, but from DOL 80, the patient started to have cyanotic spells after crying. Because noninvasive positive airway pressure was not effective in preventing these cyanotic spells, a tracheostomy was performed on DOL 133. The results of postoperative bronchoscopy were consistent with TBM. The patient was discharged on home mechanical ventilation and was maintained in a stable respiratory condition. Evaluating pre-and postsurgical anatomical and physiological characteristics is critical in managing CDH with HPF. Our case highlights the importance of assessing airway involvement in such patients.